Preparing microencpasulated textile dyestuff for better levelness of dyeing polyamide - Vojtovič, Adam; Černý, Michal; Burgert, Ladislav; Palarčík, Jiří (University of Zagreb, 2016)
Liposomes are help particles due to change dyeing kinetic of acid dyestuff. This textile dyestuff is used for better levelness of polyamide textiles. Microencapsulation method is available for create liposomes.
Příprava mikroenkapsulovaných textilních barviv pro lepší barvitelnost polyamidových textilií
Keywords: spray drying; microencapsulation; soy lecithine; acid dyestuff; rozprašovací sušení; mikroenkapsulace; sójový lecithin; kyselé barvivo